Dissatisfaction Attributions and Complaining Behavior Of Public Library Users - Suki, Norazah Mohd (Information Management and Business Review, 2010)
This study investigates the dissatisfaction attributions and complaining behavior of public library users. This paper analyses a survey of ninety-nine randomly selected public library users in the Federal Territory of Labuan, Malaysia. Data was analyzed using multiple regression analysis. The survey revealed that public library users in the Federal Territory of Labuan, Malaysia, who believe that service failure is due to the negligence of library staff and perceive the service of the library to be free, are more likely to complain to a third party. Loyal users also prefer to complain to a third party about their dissatisfaction. Some users complain directly to the personnel or person in charge of the department or chief librarian at the time of dissatisfaction. Users’ complaints can be a powerful resource for the library management to use in making strategic and tactical decisions that could prevent them from switching services or performing actions such as abandoning the library and no longer using library services.